Financial Analysis of Airlines As Air Cargo Terminal Operator (The Case of Garuda Indonesia) - ., Raniyah; Abdul Chalid, Dony (KnE Social Sciences, 2020)
PT. Garuda Indonesia Tbk is the only one of the airlines in Indonesia that operates as non-integrated cargo services and manages air cargo terminal service. This study aims to assess and evaluate the business model of airlines as an air cargo terminal operator. Correspondingly, to analyze the business model, the airline is run as an air cargo terminal operator on its own compared to if the cargo services outsourced to other parties at the terminal. The analysis will conduct by performing financial analysis and comparative study analysis. After that, scenario analysis will lead and decided the priority of air cargo business. The result is when the company decides to outsource the business to the other party is better than if they run by themselves. From scenario analysis results, it shows that all the scenarios of the outsourced still better compared to if they run their business by themselves. Keywords: Air Cargo, Terminal Operator, Financial Analysis, Warehouse Revenue, Comparative Study, Scenario Analysis